A phenolic polymer lithium salt lithium supplementing agent, a preparation method and application thereof

CN123003801APending Publication Date: 2026-10-30SHANDONG TAIHE WATER TREATMENT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611046403.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其中,五铁酸锂、镍酸锂、硅酸锂等无机补锂材料补锂容量高、稳定性好,但存在易吸潮水解、加工窗口窄、体系脱锂不完全等问题

Benefits of technology

本发明提供的酚醛聚合物锂盐补锂剂,可以在锂电池首次充放电过程中有效补充活性锂,提高电池的首次库伦效率;该补锂剂通过控制反应条件,实现以线性聚合为主,部分平面交联和少量体型交联为辅,形成相互连接的π稠环面结构,可以稳定层间隙,促进锂离子在间隙内部的扩散速率,提高电池能量密度;该补锂剂通过相互连接的π稠环面结构提高了热稳定性和化学稳定性,不易被液态电解液溶解,缓解体积膨胀和SEI膜不稳定问题,进而提升锂电池的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The application discloses a phenolic polymer lithium salt lithium supplement agent, a preparation method and application thereof, and is prepared from phenolic, formaldehyde and lithium hydroxide phosphate as raw materials. The lithium supplement agent effectively supplements active lithium in the first charge-discharge process of a lithium battery, and improves the first coulomb efficiency of the battery. The lithium supplement agent realizes linear polymerization as the main method, partial planar crosslinking and a small amount of body crosslinking as the auxiliary method by controlling reaction conditions, forms a mutual connection pi fused ring surface structure, can stabilize the interlayer gap, promotes the diffusion rate of lithium ions in the gap, and improves the energy density of the battery. The lithium supplement agent improves the thermal stability and chemical stability through the mutual connection pi fused ring surface structure, is not easy to be dissolved by a liquid electrolyte, alleviates the problems of volume expansion and unstable SEI film, and further improves the cycle performance of the lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, and specifically relates to a phenolic polymer lithium salt lithium supplement agent, its preparation method and application. Background Technology

[0002] Lithium-ion batteries are widely used in new energy power batteries, large-scale energy storage systems, and portable electronic devices. Among them, lithium iron phosphate batteries are stable in structure, have excellent cycle life, low raw material cost, and are environmentally friendly, making them the mainstream battery system for current energy storage batteries and economical power batteries. During the initial formation of a lithium-ion battery, an electrolyte reduction reaction occurs on the surface of the negative electrode, forming a dense solid electrolyte interface (SEI) film. The formation of the SEI film can passivate the negative electrode interface and inhibit the continuous decomposition of the electrolyte, which is a necessary structure to ensure stable battery cycling. However, this film formation process irreversibly consumes a large amount of active lithium source inside the battery, causing permanent lithium loss and resulting in significant initial capacity decay. The irreversible lithium loss of conventional graphite negative electrode systems can reach 6% to 12%, while the irreversible lithium loss of silicon-based negative electrodes can be as high as 15% to 25% due to the dramatic volume expansion and continuous interface reconstruction. Lithium iron phosphate itself has limited lithium reserves and cannot provide a surplus lithium source to compensate for the consumption of the SEI film in the negative electrode. This results in generally low initial coulombic efficiency of the full cell and a significant decrease in effective energy density. Furthermore, the continuous shortage of lithium source during cycling accelerates the capacity decay of the battery, thus restricting the further development of high-life and high-energy-density lithium batteries.

[0003] To address the issues of low initial efficiency and insufficient active lithium, the industry has gradually developed pre-lithiation and lithium replenishment technologies. Traditional pre-lithiation methods include positive electrode pre-lithiation and negative electrode pre-lithiation. Through technological research, positive electrode lithium replenishment technology, with its strong compatibility, high safety, and controllable cost, has become the mainstream technology in this field. Positive electrode lithium replenishment technology, by adding sacrificial lithium-rich additives to the positive electrode slurry, can release active lithium in advance during the first charge of the battery, directionally compensating for irreversible lithium loss in the SEI film. It requires no modification to existing production lines, and the process is simple, widely adaptable, and highly safe. Currently, publicly available positive electrode lithium replenishment materials mainly include two categories: inorganic lithium-rich oxides and organic lithium salts. Among them, inorganic lithium replenishment materials such as lithium pentferrate, lithium nickelate, and lithium silicate have high lithium replenishment capacity and good stability, but suffer from problems such as easy moisture absorption and hydrolysis, narrow processing window, and incomplete delithiation. Organic lithium replenishment agents such as lithium oxalate and lithium squaric acid, while having better process compatibility, suffer from defects such as decomposition voltage mismatch, poor thermal stability, low lithium replenishment efficiency, and large gas production.

[0004] In summary, existing cathode lithium replenishment materials generally suffer from a technical dilemma: it is difficult to simultaneously achieve high initial efficiency, thermal stability, processing compatibility, low-temperature performance, and gas generation characteristics. A single lithium replenishment material cannot simultaneously meet the industrial demands for high initial efficiency, long cycle life, low gas generation, wide temperature range, and low cost. Therefore, developing a novel organic cathode lithium replenishment agent with high voltage matching, good thermal stability, excellent process compatibility, controllable byproducts, and the ability to significantly improve the initial coulombic efficiency and cycle stability of batteries has significant engineering value and market application prospects. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a phenolic polymer lithium salt lithium replenisher, its preparation method, and its application. A partially cross-linked phenolic polymer is generated through the reaction of hydroquinone, formaldehyde aqueous solution, and lithium hydroxide. This lithium replenisher exhibits high specific capacity and strong stability. By forming stable spatial channels, it promotes the diffusion rate of lithium ions within the positive electrode, effectively replenishing lithium ion losses during the first charge and discharge cycle, thereby significantly improving the battery's energy density and lifespan.

[0006] This invention is achieved through the following technical solution: The phenolic polymer lithium salt lithium supplement of this invention has the following general structural formula: Wherein, P is any one of catechol dilithium, resorcinol dilithium, or hydroquinone dilithium, a is the molar ratio of methylene to P in the polymer unit, with a ratio of 1.2 to 1.5, and n is the degree of polymerization, with a value ∈ (30, 70).

[0007] According to the aforementioned phenolic polymer lithium salt lithium supplement, where P is resorcinol disilicide, the structural diagram of this lithium supplement is as follows: .

[0008] This invention discloses a method for preparing a phenolic polymer lithium salt lithium supplement, comprising the following steps: S 1. Add a measured amount of hydroquinone and deionized water to the reaction vessel and stir to dissolve at room temperature for 10-20 minutes. Then, add lithium hydroxide aqueous solution dropwise to adjust the pH value to 8.5-9.5. During the dropwise addition process, control the neutralization temperature at 30-50℃. After the pH value is adjusted, continue stirring and neutralizing the reaction for 10-20 minutes. S 2. Control the temperature inside the reactor within a certain range, then add a quantitative formaldehyde solution dropwise at a certain flow rate. The addition is completed in 1~2 hours. Continue to maintain the temperature inside the reactor as described above. After keeping the temperature for 2~3 hours, evaporate the water and free formaldehyde under a pressure of -0.08~-0.09MPa. After mechanical crushing, pass the solution through a 20-mesh sieve, and then crush it with nitrogen gas flow to obtain the target phenolic polymer lithium salt.

[0009] According to the preparation method of the phenolic polymer lithium salt lithium supplement, the hydroquinone in step S1 is one of catechol, resorcinol or hydroquinone, the amount of deionized water is 2 to 3 times the mass of hydroquinone, and the content of the lithium hydroxide aqueous solution is 5 to 10%.

[0010] According to the preparation method of the phenolic polymer lithium salt lithium supplement, the formaldehyde solution in step 2 has a content of 37%, and the molar ratio of hydroquinone to formaldehyde is 1:(1.2~1.5).

[0011] According to the preparation method of the phenolic polymer lithium salt lithium supplement, the temperature inside the reactor in step S2 is adjusted according to the type of hydroquinone used: when using catechol, the temperature inside the reactor is controlled at 45~55℃; when using resorcinol, the temperature inside the reactor is controlled at 10~15℃; when using hydroquinone, the temperature inside the reactor is controlled at 20~30℃.

[0012] According to the preparation method of the phenolic polymer lithium salt lithium supplement, the operating parameters of the nitrogen gas flow pulverization in step S2 are: pulverization pressure 0.6~0.8Mpa, feeding speed 5~10kg / h, and classifier speed 8000~12000rpm.

[0013] According to the preparation method of the phenolic polymer lithium salt lithium supplement, the particle size of the phenolic polymer lithium salt in step S2 is D100∈1~20μm and D50∈5~8μm.

[0014] This invention relates to the application of phenolic polymer lithium salt lithium supplement in the positive electrode of lithium batteries.

[0015] 1. According to the application, the phenolic polymer lithium salt supplement is added to the positive electrode material of a lithium battery to make a positive electrode for use in a lithium battery, and the amount of the phenolic polymer lithium salt supplement added to the positive electrode material is 3~5wt.

[0016] Beneficial effects of this invention: The phenolic polymer lithium salt lithium replenisher provided by this invention can effectively replenish active lithium during the first charge and discharge of a lithium battery, thereby improving the battery's initial coulombic efficiency. This lithium replenisher, by controlling reaction conditions, achieves a predominantly linear polymerization with some planar crosslinking and a small amount of bulk crosslinking, forming an interconnected π-fused toroidal structure. This stabilizes the interlayer gaps, promotes the diffusion rate of lithium ions within the gaps, and increases the battery's energy density. Furthermore, the interconnected π-fused toroidal structure enhances the lithium replenisher's thermal and chemical stability, making it less susceptible to dissolution by liquid electrolytes, alleviating volume expansion and SEI film instability issues, and ultimately improving the cycle performance of the lithium battery. Detailed Implementation

[0017] The following is a further explanation of the content of this invention: The phenolic polymer lithium salt lithium supplement of this invention has the following general structural formula: Wherein, P is any one of catechol dilithium, resorcinol dilithium, or hydroquinone dilithium, a is the molar ratio of methylene to P in the polymer unit, with a ratio of 1.2 to 1.5, and n is the degree of polymerization, with a value ∈ (30, 70).

[0018] Using resorcinol dilithium as an example, the structural diagram of this lithium supplement is as follows: .

[0019] The preparation method of the phenolic polymer lithium salt lithium supplement of the present invention includes the following steps: S 1. Add a measured amount of hydroquinone and deionized water to a reaction vessel and stir to dissolve at room temperature for 10-20 minutes. Then, add lithium hydroxide aqueous solution dropwise to adjust the pH value to 8.5-9.5. During the dropwise addition process, control the neutralization temperature at 30-50℃. After the pH value is adjusted, continue stirring and neutralizing the reaction for 10-20 minutes. The hydroquinone is one of catechol, resorcinol, or hydroquinone. The amount of deionized water is 2-3 times the mass of hydroquinone, and the content of the lithium hydroxide aqueous solution is 5-10%.

[0020] S2. Control the temperature inside the reactor within a certain range, then add a quantitative formaldehyde solution at a certain flow rate. The formaldehyde content of the solution is 37%, and the molar ratio of hydroquinone to formaldehyde is 1:(1.2~1.5). After 1~2 hours of addition, maintain the reactor temperature for 2~3 hours. Then, under a pressure of -0.08~-0.09 MPa, externally distill off water and free formaldehyde. After mechanical pulverization and passing through a 20-mesh sieve, the mixture is then pulverized with nitrogen gas to obtain the target phenolic polymer lithium salt with particle sizes D100∈1~20μm and D50∈5~8μm. The operating parameters for nitrogen gas pulverization are: pulverization pressure 0.6~0.8 MPa, feed rate 5~10 kg / h, and classifier wheel speed 8000~12000 rpm.

[0021] In step S2, the temperature inside the reactor is adjusted according to the type of hydroquinone used: when using catechol, the temperature inside the reactor is controlled at 45~55℃; when using resorcinol, the temperature inside the reactor is controlled at 10~15℃; when using hydroquinone, the temperature inside the reactor is controlled at 20~30℃.

[0022] The preparation of the phenolic polymer lithium salt of the present invention will be described below with specific parameters: All raw materials used in this invention are commercially available, with the formaldehyde solution having a mass fraction of 37%; a 10% lithium hydroxide aqueous solution was prepared in-house for later use; the parameters for air jet milling were set as follows: milling pressure 0.7 MPa, feeding speed 5 kg / h, and classifying wheel speed 10000 r / min.

[0023] Example 1

[0024] Step S1: Add 110.1g of catechol and 220.2g of deionized water to the reaction vessel and stir at room temperature for 15±5min. Start adding lithium hydroxide aqueous solution dropwise at a rate of 5g / min, controlling the neutralization temperature at 30~50℃ during the dropwise addition process. Add until the pH value of the solution in the vessel is 8.90 and does not decrease within 2 minutes, then stop the dropwise addition and continue stirring for 15±5min.

[0025] Step 2: Control the temperature inside the reactor at 50±5℃, add 97.4g of formaldehyde solution dropwise at a rate of 1.62g / min, and finish the addition after 1 hour. Continue to keep the temperature at 50±5℃ for 2 hours. Transfer the reaction material to a rotary evaporator and evaporate it externally at a pressure of -0.08MPa for 6 hours to remove water and trace amounts of free formaldehyde. The remaining solid is mechanically crushed and passed through a 20-mesh sieve. Then, it is pulverized with a nitrogen gas flow to obtain 136.5g of catechol formaldehyde resin dilithium salt, denoted as L.

[0026] The product was tested and found to have a moisture content of 0.005%; the particle size D50 was 6.44 μm and the D100 was 10.87 μm.

[0027] Example 2

[0028] Step 1: Add 110.1g of catechol and 330.3g of deionized water to the reaction vessel and stir at room temperature for 15±5min. Start adding lithium hydroxide aqueous solution dropwise at a rate of 5g / min, controlling the neutralization temperature at 30~50℃ during the dropwise addition process. Add until the pH value of the solution in the vessel is 9.01 and does not decrease within 2 minutes, then stop the dropwise addition and continue stirring for 15±5min.

[0029] Step 2: Control the temperature inside the reactor at 50±5℃, add 121.7g of formaldehyde solution dropwise at a rate of 1.01g / min, and finish the addition after 2 hours. Continue to keep the temperature at 50±5℃ for 3 hours. Transfer the reaction material to a rotary evaporator and evaporate externally at a pressure of -0.09MPa for 4 hours to remove water and trace amounts of free formaldehyde. The remaining solid is mechanically crushed and passed through a 20-mesh sieve. Then, it is pulverized with nitrogen gas to obtain 140.4g of catechol formaldehyde resin dilithium salt.

[0030] The product was tested and found to have a moisture content of 0.003%; a particle size D50 of 6.17 μm and a D100 of 9.62 μm.

[0031] Example 3

[0032] Step 1: Add 110.1g of resorcinol and 220.2g of deionized water to the reaction vessel and stir at room temperature for 15±5min. Start adding lithium hydroxide aqueous solution dropwise at a rate of 5g / min, controlling the neutralization temperature at 30~50℃ during the dropwise addition process. Add until the pH value of the solution in the vessel is 8.98 and does not decrease within 2 minutes, then stop the dropwise addition and continue stirring for 15±5min.

[0033] Step 2: Control the temperature inside the reactor at 10~15℃, add 97.4g of formaldehyde solution dropwise at a rate of 1.62g / min, and finish the addition after 1 hour. Continue to keep the temperature at 10~15℃ for 2 hours. Transfer the reaction material to a rotary evaporator and evaporate it externally at a pressure of -0.08MPa for 6 hours to remove water and trace amounts of free formaldehyde. The remaining solid is mechanically crushed and passed through a 20-mesh sieve. Then, it is pulverized with nitrogen gas to obtain 136.6g of resorcinol formaldehyde resin dilithium salt, denoted as J.

[0034] The product was tested and found to have a moisture content of 0.004%; a particle size D50 of 7.39 μm and a D100 of 12.54 μm.

[0035] Example 4

[0036] Step 1: Add 110.1g of resorcinol and 330.3g of deionized water to the reaction vessel and stir at room temperature for 15±5min. Start adding lithium hydroxide aqueous solution dropwise at a rate of 5g / min, controlling the neutralization temperature at 30~50℃ during the dropwise addition process. Add until the pH value of the solution in the vessel is 9.05 and does not decrease within 2 minutes, then stop the dropwise addition and continue stirring for 15±5min.

[0037] Step 2: Control the temperature inside the reactor at 10~15℃, add 121.7g of formaldehyde solution dropwise at a rate of 1.01g / min, and finish the addition after 2 hours. Continue to keep the temperature at 10~15℃ for 3 hours. Transfer the reaction material to a rotary evaporator and evaporate externally at a pressure of -0.09MPa for 4 hours to remove water and trace amounts of free formaldehyde. The remaining solid is mechanically crushed and passed through a 20-mesh sieve. Then, it is pulverized with nitrogen gas to obtain 140.5g of resorcinol formaldehyde resin dilithium salt.

[0038] The product was tested and found to have a moisture content of 0.004%; a particle size D50 of 7.11 μm and a D100 of 11.95 μm.

[0039] Example 5

[0040] Step 1: Add 110.1g hydroquinone and 220.2g deionized water to the reaction vessel and stir at room temperature for 15±5min. Start adding lithium hydroxide aqueous solution dropwise at a rate of 5g / min, controlling the neutralization temperature at 30~50℃ during the dropwise addition process. Add until the pH value of the solution in the vessel is 8.87 and does not decrease within 2 minutes, then stop the dropwise addition and continue stirring for 15±5min.

[0041] Step 2: Control the temperature inside the reactor at 25±5℃, add 97.4g of formaldehyde solution dropwise at a rate of 1.62g / min, and finish the addition after 1 hour. Continue to keep the temperature at 25±5℃ for 2 hours. Transfer the reaction material to a rotary evaporator and evaporate it externally for 6 hours under a pressure of -0.08MPa to remove water and trace amounts of free formaldehyde. The remaining solid is mechanically crushed and passed through a 20-mesh sieve. Then, it is pulverized with a nitrogen gas flow to obtain 136.5g of hydroquinone formaldehyde resin dilithium salt, denoted as D.

[0042] The product was tested and found to have a moisture content of 0.004%; the particle size D50 was 6.72 μm and the D100 was 11.13 μm.

[0043] Example 6

[0044] Step 1: Add 110.1g hydroquinone and 330.3g deionized water to the reaction vessel and stir at room temperature for 15±5min. Start adding lithium hydroxide aqueous solution dropwise at a rate of 5g / min, controlling the neutralization temperature at 30~50℃ during the dropwise addition process. Add until the pH value of the solution in the vessel is 9.10 and does not decrease within 2 minutes, then stop the dropwise addition and continue stirring for 15±5min.

[0045] Step 2: Control the temperature inside the reactor at 25±5℃, add 121.7g of formaldehyde solution dropwise at a rate of 1.01g / min, and finish the addition after 2 hours. Continue to keep the temperature at 25±5℃ for 3 hours. Transfer the reaction material to a rotary evaporator and evaporate externally at a pressure of -0.09MPa for 4 hours to remove water and trace amounts of free formaldehyde. The remaining solid is mechanically crushed and passed through a 20-mesh sieve. Then, it is pulverized with nitrogen gas to obtain 140.4g of hydroquinone formaldehyde resin dilithium salt.

[0046] The product was tested and found to have a moisture content of 0.005%; the particle size D50 was 6.54 μm and the D100 was 10.99 μm.

[0047] Application of the phenolic polymer lithium salt of this invention Preparation of positive electrode: Compound lithium iron phosphate (LFP), polyvinylidene fluoride (PVDF), and conductive carbon black (Sp) are mixed evenly in N-methylpyrrolidone (NMP) solution at a mass ratio of 94:3:3. The mass ratio of lithium iron phosphate (LFP) to L / J / D in the compound lithium iron phosphate (LFP) is 95:5. Then, it is coated onto aluminum foil. After drying the aluminum foil in a vacuum oven at 120℃, it is cut into positive electrode sheets containing lithium supplementation agent with a diameter of 1.2cm and sealed for storage. Another type of positive electrode sheet is prepared by replacing the compound LFP with LFP, while keeping other conditions unchanged, to obtain a blank positive electrode sheet.

[0048] Preparation of negative electrode sheet: Graphite QCG-X9, SP, CMC, SBR and LA136D were mixed evenly in deionized water at a mass ratio of 96:1:1:1:1 and then vacuum degassed. The slurry was then coated on the surface of Cu foil and dried in a vacuum oven at 80℃ for 2 hours to obtain negative electrode sheet. The negative electrode sheet was then rolled and cut into negative electrode sheets with a diameter of 1.4 cm and sealed for storage.

[0049] Assembly and testing of the full battery: LFP, LFP+L, LFP+J, and LFP+D positive electrode sheets were assembled with QCG-X9 negative electrode sheets to form CR2032 batteries. The ratio of the unit area capacity of the negative electrode sheet to the unit area capacity of the positive electrode sheet was 1.5:1.00. Charge and discharge tests were conducted on the LANBTS test cabinet within the voltage range of 2.5-3.8 V.

[0050] The test results are shown in the table below: , .

[0051] The results in Tables 1 and 2 show that the lithium battery using the phenolic polymer dilithium salt provided by this invention as the positive electrode lithium replenisher has a significantly higher initial charge-discharge specific capacity than the lithium battery without the lithium replenisher. Its initial coulombic efficiency is increased from 80% to over 90%, which effectively improves the energy density of the lithium battery, while also improving the capacity retention rate and extending the battery life.

[0052] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A phenolic polymer lithium salt lithium supplement agent, characterized in that its... The general structural formula is Wherein, P is any one of catechol dilithium, resorcinol dilithium, or hydroquinone dilithium, a is the molar ratio of methylene to P in the polymer unit, with a ratio of 1.2 to 1.5, and n is the degree of polymerization, with a value ∈ (30, 70).

2. The phenolic polymer lithium salt lithium supplement agent according to claim 1, characterized in that, P stands for lithium resorcinol. The structural diagram of this lithium supplement is as follows: .

3. A method for preparing a phenolic polymer lithium salt lithium supplement according to claim 1 or 2, characterized in that, Includes the following steps: S 1. Add a measured amount of hydroquinone and deionized water to the reaction vessel and stir to dissolve at room temperature for 10-20 minutes. Then, add lithium hydroxide aqueous solution dropwise to adjust the pH value to 8.5-9.

5. During the dropwise addition process, control the neutralization temperature at 30-50℃. After the pH value is adjusted, continue stirring and neutralizing the reaction for 10-20 minutes. S 2. Control the temperature inside the reactor within a certain range, then add a quantitative formaldehyde solution dropwise at a certain flow rate. The addition is completed in 1~2 hours. Continue to maintain the temperature inside the reactor as described above. After keeping the temperature for 2~3 hours, evaporate the water and free formaldehyde under a pressure of -0.08~-0.09MPa. After mechanical crushing, pass the solution through a 20-mesh sieve, and then crush it with nitrogen gas flow to obtain the target phenolic polymer lithium salt.

4. The method for preparing a phenolic polymer lithium salt lithium supplement according to claim 3, characterized in that, In step S1, the hydroquinone is one of catechol, resorcinol, or hydroquinone, the amount of deionized water is 2 to 3 times the mass of hydroquinone, and the content of the lithium hydroxide aqueous solution is 5 to 10%.

5. The method for preparing a phenolic polymer lithium salt lithium supplement according to claim 3, characterized in that, The formaldehyde solution in step 2 has a content of 37%, and the molar ratio of hydroquinone to formaldehyde is 1:(1.2~1.5).

6. The method for preparing a phenolic polymer lithium salt lithium supplement according to claim 4, characterized in that, The temperature inside the reactor in step S2 is adjusted according to the type of hydroquinone used: when using catechol, the temperature inside the reactor is controlled at 45~55℃; when using resorcinol, the temperature inside the reactor is controlled at 10~15℃; when using hydroquinone, the temperature inside the reactor is controlled at 20~30℃.

7. The method for preparing a phenolic polymer lithium salt lithium supplement according to claim 3, characterized in that, The operating parameters for nitrogen gas flow pulverization in step S2 are: pulverization pressure 0.6~0.8Mpa, feeding speed 5~10kg / h, and classifying wheel speed 8000~12000rpm.

8. The method for preparing a phenolic polymer lithium salt lithium supplement according to claim 3, characterized in that, The particle size of the phenolic polymer lithium salt in step S2 is D100∈1~20μm and D50∈5~8μm.

9. The application of the phenolic polymer lithium salt lithium supplement agent according to claim 1 or 2 in the positive electrode of a lithium battery.

10. The application according to claim 9, characterized in that, The phenolic polymer lithium salt supplement is added to the positive electrode material of a lithium battery to form a positive electrode for use in a lithium battery. The amount of the phenolic polymer lithium salt supplement added to the positive electrode material is 3~5wt.